2012
DOI: 10.1186/1471-230x-12-25
|View full text |Cite
|
Sign up to set email alerts
|

Early effect of oral administration of omeprazole with mosapride as compared with those of omeprazole alone on the intragastric pH

Abstract: BackgroundThe ideal medication for acid-related diseases should have a rapid onset of action to promote hemostasis and cause efficient resolution of symptoms. The aim of our study was to comparatively investigate the inhibitory effect on gastric acid secretion of a single oral administration of omeprazole plus mosapride with that of omeprazole alone.MethodsTen Helicobacter pylori-negative male subjects participated in this randomized, two-way crossover study. Intragastric pH was monitored continuously for 6 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Consequently, for the resolution of heartburn symptoms, the rapid suppression of gastric acid secretion is one of the most important factors [ 23 ]. Because omeprazole with mosapride increases the intragastric pH immediately [ 10 ], it was naturally recognized as a useful on-demand therapy for patients with mild GERD. Rabeprazole with mosapride might accelerate the onset of action; it might be more suitable for on-demand therapy than rabeprazole alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, for the resolution of heartburn symptoms, the rapid suppression of gastric acid secretion is one of the most important factors [ 23 ]. Because omeprazole with mosapride increases the intragastric pH immediately [ 10 ], it was naturally recognized as a useful on-demand therapy for patients with mild GERD. Rabeprazole with mosapride might accelerate the onset of action; it might be more suitable for on-demand therapy than rabeprazole alone.…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that the oral administration of H2RA with mosapride increased the intragastric pH more rapidly than H2RA alone [ 9 ]. In addition, our previous study showed that omeprazole orally administered 1 h after mosapride increased the intragastric pH more rapidly than omeprazole alone [ 10 ]. However, no crossover comparisons have been reported of the acid-suppressive effect of oral PPI with mosapride versus PPI alone.…”
Section: Introductionmentioning
confidence: 99%
“…The achlorhydria regimen consisted of omeprazole 40 mg and aluminum hydroxide/magnesium hydroxide 200/400 mg administration 3 h prior to each EDP1066 dose. Both drugs increase the gastric pH ( 44 46 ) and were expected to improve the transition of EDP1066 through the stomach and into the duodenum. Omeprazole and aluminum hydroxide/magnesium hydroxide are not known to induce immune system modulation.…”
Section: Methodsmentioning
confidence: 99%
“…Mosapride is less effective than PPI as monotherapy in the management of GERD and is usually used as an adjunct to PPI therapy. Coadministration of mosapride has favorable influence on pharmacokinetics of PPI by accelerating the absorption of PPI and increasing maximum plasma concentration and the area under the time-plasma concentration curve and combination therapy with mosapride and PPI increases intragastric pH more rapidly than using PPI alone [101, 102]. However, mosapride as add-on therapy to PPI in patients with erosive esophagitis fails to provide better symptom relief than placebo, and additional benefits of mosapride are only possibly seen in patients with severe symptoms [103].…”
Section: Therapy Focused On Gastroesophageal Motilitymentioning
confidence: 99%